Involvement of Astrocytes in Alzheimer’s Disease from a Neuroinflammatory and Oxidative Stress Perspective - González-Reyes, Rodrigo E.; Nava-Mesa, Mauricio O.; Vargas-Sánchez, Karina; Ariza-Salamanca, Daniel; Mora-Muñoz, Laura (Frontiers in Molecular Neuroscience, 2017)
Alzheimer disease (AD) is a frequent and devastating neurodegenerative disease in humans, but still no curative treatment has been developed. Although many explicative theories have been proposed, precise pathophysiological mechanisms are unknown. Due to the importance of astrocytes in brain homeostasis they have become interesting targets for the study of AD. Changes in astrocyte function have been observed in brains from individuals with AD, as well as in AD in vitro and in vivo animal models. The presence of amyloid-beta (Aβ) has been shown to disrupt gliotransmission, neurotransmitter uptake, and alter calcium signaling in astrocytes. Furthermore, astrocytes express ApoE protein and are involved in the production, degradation and removal of Aβ. As well, changes in astrocytes that precede other pathological characteristics observed in AD, point to an early contribution of astroglia in this disease. Astrocytes participate in the inflammatory/immune responses of the CNS. The presence of Aβ activates different cell receptors and intracellular signaling pathways, mainly the RAGE/NF-κB pathway, responsible for the transcription of pro-inflammatory cytokines and chemokines in astrocytes. The release of these pro-inflammatory agents may induce cellular damage or even stimulate the production of Aβ in astrocytes. Additionally, Aβ induces the appearance of oxidative stress and production of ROS and RNS in astrocytes, affecting among others, intracellular calcium levels, NADPH oxidase, NF-κB signaling, glutamate uptake (increasing the risk of excitotoxicity) and mitochondrial function. Excessive neuroinflammation and oxidative stress are observed in AD, and astrocytes seem to be involved in both. The Aβ/NF-κB interaction in astrocytes may play a central role in these inflammatory and oxidative stress changes present in AD. In this paper, we also discuss therapeutic measures highlighting the importance of astrocytes in AD pathology. Several new therapeutic approaches involving phenols (curcumin), phytoestrogens (genistein), neuroesteroids and other natural phytochemicals have been explored in astrocytes, obtaining some promising results regarding cognitive improvements and attenuation of neuroinflammation. Novel strategies comprising astrocytes and aimed to reduce oxidative stress in AD have also been proposed. These include estrogen receptor agonists (pelargonidin), Bambusae concretio Salicea, Monascin and various antioxidatives such as resveratrol, tocotrienol, anthocyanins and epicatechin, showing beneficial effects in AD models.